PENGARUH KADAR AIR KAPASITAS LAPANG TERHADAP PERTUMBUHAN BEBERAPA GENOTIPE M3 KEDELAI (Glycine max L. Merr) - Sasmi Rais Siregar; Zuraida Zuraida; Zuyasna Zuyasna (Jurnal Floratek, 2017)
The purpose of this research is to know the effect of moisture content of field capacity on the growth of several mutant genotypes of 3rd generation (M3) Kipas Merah soybean varieties. The research was conducted at Screen House and Soil Chemistry Laboratory  Faculty of Agriculture Syiah Kuala Universtity from May to Jun 2015. The experimental Randomized Block Design (CRBD) factorial was used, consisting of two factors and three replications. The first factor was based on the field capacity level, consisting of 100%, 80%, 60%, and 40%, and the second factor consisted of 14 mutants of 3rd generation Kipas Merah and the original Kipas Merah variety as control. The results showed that the interaction between field capacity and soybean genotype significantly affected the growth of soybean crops. In a 40% field capacity treatment of almost all the parameters tested the genotype showed no significant difference, howeverKM300-38 showed the highest plant among the genotypes tested. In a 60% of field capacity, genotype KM200-18 and KM200-37 showed better growth on all parameters tested, although not significantly different from genotype KM200-9, KM200-41, and KM300-9. Genotypes of mutant soybean that can survive and provide good growth in water shortage are KM200-18, KM200-37, KM200-9, KM300-9, and KM200-41.Selection of drought-tolerant genotypes can be performed under 40% of the field capacity.